Crystallinity of regenerated cellulose from [Bmim]Cl dependent on the hydrogen bond acidity/basicity of anti-solvents. Issue 65 (22nd August 2017) - Fan, Zhaosheng; Chen, Jianbo; Guo, Wenji; Ma, Fang; Sun, Suqin; Zhou, Qun
Abstract : Attenuated total reflection Fourier transform infrared (ATR-FTIR) spectroscopy was used to monitor the molecular diffusion processes of four anti-solvents in situ . Abstract : Cellulose, regarded as a potential sustainable resource for the future, can dissolve and regenerate in ionic liquids (ILs) upon adding anti-solvents. Improving the regeneration conditions, like changing the anti-solvents, could optimize the properties of regenerated cellulose-based materials. Previous studies pointed out that the diffusion processes of anti-solvents plays a significant role in the determination of the properties of regenerated cellulose fibers/films. However, the cellulose regeneration mechanism from ILs has not been clarified. Here, attenuated total reflection Fourier transform infrared (ATR-FTIR) spectroscopy was introduced to monitor the molecular diffusion processes of four anti-solvents in situ . The crystallinity of regenerated cellulose showed a negative correlation with respect to the diffusion coefficient. In addition, the interaction of imidazolium cations and anti-solvent molecules was evaluated from the peak shifting during the diffusion processes. Furthermore, Taft and Kamlet scales were used to quantify the interaction between IL cations/anions and anti-solvent molecules, eliciting distinct cellulose regeneration paths in different anti-solvents.